Safe space for traumatic urban youths - Yen, Kok Hui; Mohd Noor, Mohd Zairul (Human Resources Management Academic Research Society (HRMARS), 2024)
For traumatized urban youths, a youth safe space can be access to refuge, a place where they feel safe and protected, as well as being comfortable in their own skin. Youth require secure public areas to congregate, participate in activities catering to their wide range of needs and interests, influence decisions, and express themselves freely. The traumas and mental health problems affecting today’s youth are brought to light in this safe space environment, along with what the community can do to support them. However, there is no specific design or guideline for trauma-oriented design to create a safe space for traumatic urban youths. Therefore, this research will formulate trauma-informed design approaches that create a safe space for urban youths. This research will produce a safe space in the rehabilitation design framework for traumatic youths in urban areas. This study will also identify the needs of the traumatic community and trauma-informed design in community-based rehabilitation that will help the community cope with life’s stresses and work productively. Future research can conduct a qualitative study to examine the interface between community-based rehabilitation and trauma-informed design in a safe space.